Spatial patterns of distribution and relative abundance of coastal shark species in the Galapagos Marine Reserve - Acuña-Marrero, D.; Smith, A.; Salinas-De-León, P.; Harvey, Euan; Pawley, M.; Anderson, M. (Inter-Research, 2018)
A better understanding of the patterns of distribution and abundance of sharks and their potential biological and environmental drivers is essential to develop and evaluate spatial management plans for conservation and fisheries. Benthic and pelagic baited remote underwater stereo-video systems (stereo-BRUVs) were used to describe spatial and temporal patterns in coastal shark assemblages in the Galapagos Marine Reserve (GMR). From 629 stereo-BRUV deployments, 877 sharks from 10 species were recorded. Shark assemblages displayed high spatial variation, likely in response to the diversity of habitats occurring in the GMR. The relative importance of environmental and biological drivers differed among shark species according to their mobility. Some species were widespread across the Galapagos Archipelago (GA) but oc - curred primarily only as either juveniles (Carcharhinus galapagensis) or adults (C. limbatus and Triaenodon obesus), while others were more spatially restricted and associated with geographical features (Sphyrna lewini and Galeocerdo cuvier) or specific habitats (Triakidae spp. and Hetero - dontus quoyi). The highest diversity of sharks was found in the Centre South bioregion of the GA, in areas with heterogeneous habitat and high overall fish diversity (islets and Floreana Island), while the greatest total abundance of sharks was recorded at the northern oceanic islands of Darwin and Wolf. Overall, the GMR harbours a unique coastal shark community that varies in composition across the GA. It is dominated by large semipelagic species but is also characterised by the presence of less mobile benthic species that are not found near other oceanic islands in the Eastern Tropical Pacific region.